Strengthening of novel TiC–AlN ceramic with in-situ synthesized Ti3Al intermetallic compound. Issue 9 (15th June 2020) - Fattahi, Mehdi; Pazhouhanfar, Yaghoub; Delbari, Seyed Ali; Shaddel, Shahrzad; Sabahi Namini, Abbas; Shahedi Asl, Mehdi
Abstract: 5 wt% AlN was added to TiC-based samples spark plasma sintered at 1900 °C under 40 MPa for 10 min. XRD and microstructural assessments confirmed the in-situ formation of Ti3 Al during the sintering process. The densification behavior and mechanical properties of the undoped and doped samples were studied to evaluate the impact of AlN addition and Ti3 Al in-situ formation on the properties of TiC ceramics. AlN had a significant influence on the relative density of TiC due to the formation of molten Al and Ti3 Al intermetallic phase, yielding a fully dense material. Reinforcing TiC with AlN and Ti3 Al led to a limited drop by around 2% in the Vickers hardness of the doped sample, but improved significantly the flexural strength up to 688 MPa. The reason for such an improvement in the flexural strength of SPSed ceramic was owing to the formation of strong diffusion bonds between secondary phases and the matrix.